DOI: 10.3990/1.9789036550338
|View full text |Cite
|
Sign up to set email alerts
|

What Works When for Whom? A methodological reflection on Therapeutic Change Process Research

Abstract: This thesis is part of the What Works When for Whom project, supported by the Life Science & eHealth domain of the Accelerating Scientific Discovery (ASDI) call from the Netherlands eScience Center (NLeSC; Amsterdam, the Netherlands): grant number 027.015.G04 awarded to dr. A. M. Sools. The NLeSC is the national knowledge center for the development and application of research software to advance scientific research, and is funded by the Netherlands Organization for Scientific Research (in Dutch: Nederlandse or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 278 publications
0
1
0
Order By: Relevance
“…In practice, when collecting or reusing patient data in the Netherlands, most data sets are too small to develop strong classification models. This limitation was seen not only in the cases presented in this dissertation; also other studies set in the Netherlands (e.g., Smink, 2021) showed that even after years of data collection, the resulting Dutch mental health intervention data set was still too small for successful supervised learning. This underlines a recurring theme throughout the chapters of this dissertation, namely that the available data sets were too small for the complex models that were fitted, and that text preprocessing tools and dictionaries were primarily developed (and sometimes only available) for the English language.…”
Section: Limitationsmentioning
confidence: 90%
“…In practice, when collecting or reusing patient data in the Netherlands, most data sets are too small to develop strong classification models. This limitation was seen not only in the cases presented in this dissertation; also other studies set in the Netherlands (e.g., Smink, 2021) showed that even after years of data collection, the resulting Dutch mental health intervention data set was still too small for successful supervised learning. This underlines a recurring theme throughout the chapters of this dissertation, namely that the available data sets were too small for the complex models that were fitted, and that text preprocessing tools and dictionaries were primarily developed (and sometimes only available) for the English language.…”
Section: Limitationsmentioning
confidence: 90%